PERSONAL HYGIENE AS A RISK FACTOR FOR STH INFECTION AMONG FARMERS IN JEMBER REGENCY - Emilia Angelica; Jauhar Firdaus; Bagus Hermansyah; Wiwien Sugih Utami; Yunita Armiyanti (Journal of Vocational Health Studies, 2026)
Background: Soil Transmitted Helminth (STH) infections remain one of the main health problems in developing countries, including Indonesia with prevalence rates ranging from 2.5% to 62%. Poor personal hygiene is a key risk factor contributing to the increased prevalence, especially among farmers. Jember Regency, an agricultural region where most residents work as farmers, presents a higher vulnerability to STH infections due to frequent contact with soil. Purpose: This study aimed to analyze the association between personal hygiene and STH infection among farmers in Jember Regency, East Java. Method: This study was a cross-sectional design involving 100 farmers selected using multistage sampling. Structured questionnaires were used for hygiene data collection. Identification of STH from fecal samples used sedimentation and flotation techniques. The relationship between hygiene practices and STH infections was tested using Cramer's V. Result: The prevalence of STH infections in farmers was 10% and all of them were hookworm infections. Most respondents, including those infected with STH, had moderate hygiene category. The results of statistical tests showed a significant relationship between personal hygiene and STH infections among farmers in Jember district. Conclusion: The strong link between personal hygiene and STH infection indicated that existing practices might not be adequate for safeguarding individuals in farming environments. On the other hand, maintaining personal hygiene was essential in the preventive approach for the farming community in Jember.